Advances in the research of immunomodulatory mechanism of mesenchymal stromal/stem cells on periodontal tissue regeneration - Zhao, De-Zhi; Yang, Rui-Lin; Wei, Han-Xiao; Yang, Kang; Yang, Yi-Bing; Wang, Nuo-Xin; Zhang, Qian; Chen, Fang; Zhang, Tao (Frontiers in Immunology, 2025)
Periodontal disease is a highly prevalent disease worldwide that seriously affects people’s oral health, including gingivitis and periodontitis. Although the current treatment of periodontal disease can achieve good control of inflammation, it is difficult to regenerate the periodontal supporting tissues to achieve a satisfactory therapeutic effect. In recent years, due to the good tissue regeneration ability, the research on Mesenchymal stromal/stem cells (MSCs) and MSC-derived exosomes has been gradually deepened, especially its ability to interact with the microenvironment of the body in the complex immunoregulatory network, which has led to many new perspectives on the therapeutic strategies for many diseases. This paper systematically reviews the immunomodulatory (including bone immunomodulation) properties of MSCs and their role in the periodontal inflammatory microenvironment, summarizes the pathways and mechanisms by which MSCs and MSC-EVs have promoted periodontal regeneration in recent years, lists potential areas for future research, and describes the issues that should be considered in future basic research and the direction of development of “cell-free therapies” for periodontal regeneration.